The anatomy of the pediatric airway: Has our knowledge changed in 120 years? A review of historic and recent investigations of the anatomy of the pediatric larynx. Issue 1 (17th November 2017) - Holzki, Josef; Brown, Karen A.; Carroll, Robert G.; Coté, Charles J.
Summary: Background: There is disagreement regarding the anatomy of the pediatric airway, particularly regarding the shape of the cricoid cartilage and the location of the narrowest portion of the larynx. Aims: The aim of this review is to clarify the origin and the science behind these differing views. Methods: We undertook a review of published literature, University Libraries, and authoritative textbooks with key search words and phrases. Results: In vivo observations suggest that the narrowest portion of the airway is more proximal than the cricoid cartilage. However, in vitro studies of autopsy specimens measured with rods or calipers, confirm that the nondistensible and circular or near circular cricoid outlet is the narrowest level. These anatomic studies confirmed the classic "funnel" shape of the pediatric larynx. In vivo studies are potentially misleading as the aryepiglottic, vestibular, and true vocal folds are in constant motion with respiration. These studies also do not consider the effects of normal sleep, inhalation agents, and comorbidities such as adenoid or tonsil hypertrophy that cause some degree of pharyngeal collapse and alter the normal movement of the laryngeal tissues. Thus, the radiologic studies suggesting that the narrowest portion of the airway is not the cricoid cartilage may be the result of an artifact depending upon which phase of respiration was imaged. Conclusion: In vivo studies do not take into account the motion of the highly pliable laryngeal upper airway structures (aryepiglottic, vestibular, and vocal folds). Maximal abduction of these structures with tracheal tubes or bronchoscopes always demonstrates a larger opening of the glottis compared to the outlet of the cricoid ring. Injury to the larynx depends upon ease of tracheal tube or endoscope passage past the cricoid cartilage and not passage through the readily distensible more proximal structures. The infant larynx is funnel shaped with the narrowest portion the circular or near circular cricoid cartilage confirmed by multiple in vitro autopsy specimens carried out over the past century.